Analyzing equity capital programs of banks for cooperatives - Ahmad, Ismail; Duct, Ken D.; Mittelhammer, Ron C. (Wiley, 1986)
Characteristics of Banks for Cooperatives term loan and equity capital programs contribute toward complex intermittent exchanges of positive and negative cash flows between the cooperative lender and borrower and complicate the analysis of the net present value and effective interest of the financing project. A multiperiod linear program was developed to analyze the effect of variations in equity capital program components on the present value of the financing project. Furthermore, the concept of a “mixed financing project” was used to analyze the effective interest rate associated with such projects.